1976
DOI: 10.1111/j.1600-0447.1976.tb00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Deposits in the Lens and Cornea of the Eye During Long‐term Chlorpromazine Medication

Abstract: Thirty patients on long-term treatment with chlorpromazine in moderate doses showed deposits in the lens, and the majority of the patients also showed deposits in the cornea. These deposits did not increase in the 13 patients who continued on chlorpromazine during an observation period of 31/2 years. Thus, when chlorpromazine is used in moderate doses, the deposits in the eyes seem to increase only up to a certain extent. Twelve patients who were switched over to thioridazine showed no change in the deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…In addition to causing a purplish skin pigmentation of sun-exposed areas including the eyelids, it may cause a pigmentation of the conjunctiva and cornea, and also anterior subcapsular cataracts (Brookes & Matoba, 1992;Rasmussen et al 1976;Siddall 1966). The conjunctival pigmentation is light brown in colour and is usually confined to the interpalpebral regions.…”
Section: Chlorpromazinementioning
confidence: 97%
“…In addition to causing a purplish skin pigmentation of sun-exposed areas including the eyelids, it may cause a pigmentation of the conjunctiva and cornea, and also anterior subcapsular cataracts (Brookes & Matoba, 1992;Rasmussen et al 1976;Siddall 1966). The conjunctival pigmentation is light brown in colour and is usually confined to the interpalpebral regions.…”
Section: Chlorpromazinementioning
confidence: 97%
“…The lens opacities can progress from being dot-like to a white, yellow, or tan stellate pattern, at which point the corneal changes become evident. 11 Gold therapy, amiodarone, and chlorpromazine have also been linked with deposits in the lens. Again these deposits rarely affect vision and do not appear to be linked to cataract formation.…”
Section: The Lensmentioning
confidence: 98%
“…The literature has associated lens opacities with cumulative dosages and duration of exposure. 15,30,31 Some studies showed that chlorpromazine at 800 mg/day for 2 years is oculotoxic, 15 while in others, chlorpromazine at 200 mg/day over 2 years caused pigmentary deposits in the lens. 14 In addition, smoking has also been associated with cataract formation and the majority of the smoking patients belong to group 1.…”
Section: Discussionmentioning
confidence: 99%